Inhibition of Neisseria gonorrhoeae isolates by Martin-Lewis medium. Epidemiology, susceptibility profile, and plasma analysis. Issue 2 (April 1982) - Miller, M A; Anderson, P; Parker, J W; Rohrer, H H
Abstract : A study was undertaken on the premise that if an increase of 1 microgram/ml in the concentration of vancomycin in Martin-Lewis medium (MLM) could improve inhibition of Gram-positive cocci, then a concomitant increase in the inhibition of gonococci could also occur. Isolates of Neisseria gonorrhoeae that failed to grow on MLM accounted for 18-5% of all positive culture results for gonorrhoea. The incidence of isolates susceptible to vancomycin was 14% and of those susceptible to trimethoprim 2.4%; one isolate was susceptible to both vancomycin and trimethoprim. The antibiotic-susceptible isolates were more frequently isolated from asymptomatic white men. Plasmid analysis showed that the 2.4-megadalton cryptic plasmic was absent in the vancomycin-susceptible isolates. The large proportion of isolates failing to grow on selective MLM has important clinical implications for the diagnosis of gonorrhea.